Urgensi Administrasi Pencatatan Nikah dalam Tinjauan Hukum Islam - Amirulkamar, Said; Kurnia, Ryzka Dwi; Mulya, Sayed Mayzar (State of Islamic Institute Langsa, 2022)
In recent decades, the pros and cons surrounding polygamy and sirri marriage in Aceh are so obvious. The situation tapered off when the Aceh MPU allowed religious marriage without being recorded in the KUA. This gap then became an interest in the community that there was a 'playfulness' between the MPU and the Acehnese elite in order to make allowances for the ASN or Aceh officials so that the sirri wife was legalized (polygamy allowed despite the status of an ASN). This article is a field research with a qualitative approach. The methodology used is a legal analysis study of Qanun Aceh. The results of the study concluded that the Aceh MPU allows marriage without a civil record is to provide relief for ordinary people who are still administratively blind. Although, it is undeniable that there are those who profit from the regulation. Therefore, MPU Aceh emphasized that it is very important for the community to understand the importance of marriage record administration, ordinary people are allowed to marry religiously but still have to do marriage registration as soon as possible (administration follows).